2021
DOI: 10.1002/cpp.2604
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control, personality and depression symptoms in cancer: Testing a moderated mediation model

Abstract: Objective: To investigate the mediator role of locus of control on the relationship between the Big Five personality traits and the manifestation of depression symptoms in cancer outpatients. Method: Participants consisted of 220 cancer outpatients (138 women and 82 men), evaluated individually at the hospital waiting room. The measures applied were as follows: The NEO-Five Factor Inventory (NEO-FFI), Multidimensional Health Locus of Control (MHLC) Scale and Hospital Anxiety and Depression Scale (HADS).Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Filipiak et al also confirmed the relationship between the control source and personality, emphasizing the close association between the individual's control source tendency and conscientiousness, openness, and agreeableness [28] . Lima et al studied cancer patients and found that control source played a mediating role between the Big Five personality traits and depression [18] . The root of the psychological control source lies in whether the individual attributes the results of behavior to internal factors or other uncontrollable external factors.…”
Section: Relationship Analysis Between Rumination Thinking and Big Fi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Filipiak et al also confirmed the relationship between the control source and personality, emphasizing the close association between the individual's control source tendency and conscientiousness, openness, and agreeableness [28] . Lima et al studied cancer patients and found that control source played a mediating role between the Big Five personality traits and depression [18] . The root of the psychological control source lies in whether the individual attributes the results of behavior to internal factors or other uncontrollable external factors.…”
Section: Relationship Analysis Between Rumination Thinking and Big Fi...mentioning
confidence: 99%
“…Research on stock investor groups highlights the correlation between psychological control sources and neuroticism, extraversion, agreeableness, and openness [17] . Lima et al, focusing on cancer groups as subjects, discovered that control sources act as mediating influences between the Big Five personalities and depression [18] . Therefore, Hypothesis 3 posits that there is a relationship between the Big Five personality and psychological control sources, and psychological control sources play an intermediary role in the association between the Big Five personality and rumination thinking.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to support women in making personalized, informed decisions regarding managing and controlling their menopausal symptoms [6,8,9]. When women believe they have control over their health, they are more likely to engage in healthy behaviors such as a balanced diet and physical activity [10,11]. In fact, the perception of Health Locus of Control (HLC) among menopausal women is crucial in promoting healthy behaviors and effectively managing menopausal symptoms [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…When women believe they have control over their health, they are more likely to engage in healthy behaviors such as a balanced diet and physical activity [10,11]. In fact, the perception of Health Locus of Control (HLC) among menopausal women is crucial in promoting healthy behaviors and effectively managing menopausal symptoms [10,12]. In other words, HLC is a key indicator used to assess womens' health beliefs and is associated with self-care and a healthy lifestyle [13].…”
Section: Introductionmentioning
confidence: 99%